How to live better life Vol-2 - S.L.Gupta (Jaipur Mark Publishers, 2023)
the mindsets; inside the mindsets; the mindsets of a champion; the truth about ability and accomplishment; mindset and leadership; mindsets in love (or not);parents,teachers,and coaches: where do mindsets come from? changing mindsets. .
Keywords: Emotions And Senses